Aortic annulus displacement assessed by contrast left ventriculography during invasive coronary angiography as a predictor of adverse events. Issue 2 (February 2017) - Kuwata, Shingo; Yoneyama, Kihei; Suzuki, Kengo; Izumo, Masaki; Mizukoshi, Kei; Koyama, Kohei; Ishibashi, Yuki; Mitarai, Takanobu; Kamijima, Ryo; Kongoji, Ken; Harada, Tomoo; Akashi, Yoshihiro J.
Abstract: Background: We propose the use of aortic annulus displacement (AAD) detected on contrast left ventriculography (LVG) during invasive coronary angiography as a marker of left ventricular (LV) long-axis shortening. In the present study, we aimed to investigate whether AAD is associated with adverse events in patients who underwent coronary angiography because of suspected coronary artery disease. Methods: In this retrospective study, we evaluated the medical records of 998 consecutive patients who underwent invasive coronary angiography and LVG. LV lengths were measured from the apex to the aortic valve insertion by using LVG images. AAD (%) was calculated as [(LV end-diastolic length − LV end-systolic length)/LV end-diastolic length] × 100. Results: The participants' median age was 67 years. Ninety-six adverse events (composite events; all-cause death, 39; congestive heart failure, 21; late revascularization, 34; and myocardial infarction, 2) were observed during a median follow-up period of 3.1 years. In multivariate Cox regression analysis, adverse events were associated with lower AAD (hazard ratio, 0.703; p  = 0.002), after adjusting for traditional risk factors and coronary artery stenosis. The area under the curve of AAD for predicting adverse events was greater than that of LV ejection fraction (0.656 vs. 0.541, p  < 0.05). Conclusions: AAD was superior to LV ejection fraction as a predictor of adverse events in patients with and without coronary arterial stenosis. AAD may be the optimal method for assessing longitudinal LV systolic function in the catheter laboratory.